Cytoplasmic membrane fluidity measurements on intact living cells of Bacillus subtilis by fluorescence anisotropy of 1,6-diphenyl-1,3,5-hexatriene - Svobodová, J; Svoboda, P (Folia microbiologica, 1988)
A method for determination of membrane fluidity (microviscosity) in Bacillus subtilis cytoplasmic membrane under in vivo conditions is described. The membranes were labelled with the hydrophobic fluorescent probe 1,6-diphenyl-1,3,5-hexatriene during the exponential phase of growth. Fluorescence anisotropy measurements were carried out in an intact cell suspension having absorbance A as high as 0.2-0.3 (corresponding to a cell concentration of 100-300/nL).
Keywords: buněčná membrána; fluidita membrány; Protoplasts; Membrane Fluidity; protoplasty; termodynamika; Kinetics; Diphenylhexatriene; Thermodynamics; Cell Membrane; fluorescenční polarizace; Bacillus subtilis; Fluorescence Polarization; kinetika; difenylhexatrien